Phenotypic analysis of tuber yield and maturityrelated traits in white yam (Dioscorea rotundata) - Sartie, A.M.; Franco, J.; Asiedu, Robert (Academic Journals, 2012)
Inadequate yield potential of available varieties and their long growth periods are two of the factors limiting yam (Dioscorea spp.) production. Identifying yield- and maturity-related traits and breeding for them will enhance production. Ten morphological/physiological traits: time of shoot emergence, time of tuber initiation, plant height, shoot dry weight, time of shoot senescence, tuber fresh weight (tuber yield), tuber number/plant, tuber parenchyma colour, tuber dry matter content and tuber dormancy period were assessed in eight accessions of D. rotundata (white Guinea yam) on the field in 2008 and 2009. Shoot dry weight and plant height were identified as the major tuber yield-related traits. Early field emergence and tuber initiation, short tuber dormancy period and low tuber dry matter content may also be related to tuber yield. High yielding accessions were low in tuber dry matter content. Moreover, early and late maturing accessions could be separated by time of attainment of uniform parenchyma colour within a tuber, length of tuber dormancy period and time of shoot senescence. Accessions were identified that may be used as parents for developing mapping populations for some of the traits assessed in the study.